Modelling of compositional gradient for reservoir fluid in a gas condensate deposit with account for scattered liquid hydrocarbons - Ekaterina V. Kusochkova; Ilya M. Indrupskii; Dmitrii V. Surnachev; Yuliya V. Alekseeva; Aleksandr N. Drozdov (Записки Горного института)
In oil and gas reservoirs with significant hydrocarbon columns the dependency of the initial hydrocarbon composition on depth – the compositional gradient – is an important factor in assessing the initial amounts of components in place, the position of the gas-oil contact, and variations of fluid properties throughout the reservoir volume. Known models of the compositional gradient are based on thermodynamic relations assuming a quasi-equilibrium state of a multi-component hydrodynamically connected hydrocarbon system in the gravity field, taking into account the influence of the natural geothermal gradient. The corresponding algorithms allow for calculation of changes in pressure and hydrocarbon fluid composition with depth, including determination of the gas-oil contact (GOC) position. Above and below the GOC, the fluid state is considered single-phase. Many oil-gas-condensate reservoirs typically have a small initial fraction of the liquid hydrocarbon phase (LHC) – scattered oil – within the gas-saturated part of the reservoir. To account for this phenomenon, a special modification of the thermodynamic model has been proposed, and an algorithm for calculating the compositional gradient in a gas condensate reservoir with the presence of LHC has been implemented. Simulation cases modelling the characteristic compositions and conditions of three real oil-gas-condensate fields are considered. The results of the calculations using the proposed algorithm show peculiarities of variations of the LHC content and its impact on the distribution of gas condensate mixture composition with depth. The presence of LHC leads to an increase in the level and possible change in the type of the fluid contact. The character of the LHC fraction dependency on depth can be different and is governed by the dissolution of light components in the saturated liquid phase. The composition of the LHC in the gas condensate part of the reservoir changes with depth differently than in the oil zone, where the liquid phase is undersaturated with light hydrocarbons. The results of the study are significant for assessing initial amounts of hydrocarbon components and potential efficiency of their recovery in gas condensate and oil-gas-condensate reservoirs with large hydrocarbon columns.